2019
DOI: 10.1371/journal.pone.0215984
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 E6/E7 expression in circulating tumor cells in oropharyngeal squamous cell cancers: A pilot study

Abstract: Objectives Human papillomavirus-related oropharyngeal squamous cell carcinoma (HPV+ OPSCC) is increasing in incidence. Although HPV+ OPSCC has favorable prognosis, 10 to 25% of HPV+ OPSCCs eventually recur. We sought to evaluate the feasibility of detection of HPV16 E6/E7 expression in Circulating Tumor Cells (CTCs) and its utility as a prognostic tool in HPV16-associated OPSCC. Materials and methods We developed a highly sensitive RT-qPCR ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Nine studies ( n = 1353, 77.6% HPV+) examined the diagnostic accuracy of HPV detection by liquid biopsy using blood samples. One study collected the blood samples both at time of diagnosis and during treatment and evaluated the accuracy of the test regardless of the time of blood collection [ 35 ], the other eight studies collected blood samples before treatment initiation [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Five studies tested HPV in plasma [ 36 , 37 , 38 , 39 , 40 ], two studies reported detection in blood [ 35 , 41 ] and two studies investigated HPV in serum [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies ( n = 1353, 77.6% HPV+) examined the diagnostic accuracy of HPV detection by liquid biopsy using blood samples. One study collected the blood samples both at time of diagnosis and during treatment and evaluated the accuracy of the test regardless of the time of blood collection [ 35 ], the other eight studies collected blood samples before treatment initiation [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Five studies tested HPV in plasma [ 36 , 37 , 38 , 39 , 40 ], two studies reported detection in blood [ 35 , 41 ] and two studies investigated HPV in serum [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies predominantly evaluated detection of circulating HPV DNA in the blood. However, one study examined the accuracy of detecting HPV16 E6/E7 expression in circulating tumour cells (CtCs) [ 41 ]. The study addressing diagnostic accuracy of HPV expression in CtCs had a significantly lower sensitivity compared to the remaining studies ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the data for post-treatment follow-up blood samples were mixed as not all patients with HPV+ tumors had detectable levels of serum HPV DNA prior to locoregional recurrence. In contrast, when using quantitative reverse transcription PCR to detect HPV16 E6/E7 expression, the presence of circulating HPV16 E6/E7 mRNA at baseline, prior to treatment, was associated with worse progression-free survival and overall survival [56]. This was similarly true of different individual studies, which found that increased levels of pre-treatment HPV16 ctDNA were correlated with worse prognosis [57], and in one study, worse TNM staging as well [58].…”
Section: Circulating Hpv Dna As a Biomarkermentioning
confidence: 96%